Nitrogen form-mediated ethylene signal regulates root-to-shoot K+ translocation via NRT1.5 - Chen, Haifei; Zhang, Quan; Wang, Xueru; Zhang, Jianhua; Ismail, Abdelbagi M.; Zhang, Zhenhua (Wiley, 2021)
Nitrogen–potassium synergistic and antagonistic interactions are the typical case of nutrient interactions. However, the underlying mechanism for the integration of the external N form into K+ homeostasis remains unclear. Here, we show that opposite effects of NO3− and NH4+ on root‐shoot K+ translocation were due to differential regulation of an ethylene signalling pathway targeting the NRT1.5 transporter. NH4+ upregulated the transcriptional activity of EIN3, but repressed the expression of NRT1.5. However, the addition of NO3− strongly suppressed the activity of EIN3, whereas its addition upregulated the expression of AtNRT1.5 and shoot K+ concentration. The 35S:EIN3/ein3eil1 plants, nrt1.5 mutants and nrt1.5/skor double mutants displayed a low K+ chlorosis phenotype, especially under NH4+ conditions with low K+ supply. Ion content analyses indicate that root‐to‐shoot K+ translocation was significantly reduced in these mutants. A Y1H assay, an EMSA and a transient expression assay confirmed that AtEIN3 protein could directly bind to the promoter of NRT1.5 to repress its expression. Furthermore, grafted plants with the roots of 35S:EIN3 and ein3eil1/nrt1.5 mutants displayed marked leaf chlorosis with a low K+ concentration. Collectively, our findings reveal that the interaction between N form and K+ was achieved by modulating root‐derived ethylene signals to regulate root‐to‐shoot K+ translocation via NRT1.5.